2020
DOI: 10.1111/ijfs.14808
|View full text |Cite
|
Sign up to set email alerts
|

Development of low‐fat chicken bologna sausages enriched with inulin, oat fibre or psyllium

Abstract: Bologna type chichen sausages were enriched with 3% or 6% inulin, oat fibre or psyllium. Sausages enriched with inulin or 3% oat fibre were compareble to control sausages in colour, texture and sensory proprieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In the study conducted by Akoglu et al (2015) in Turkish fermented sausages, addition of BC did not cause a significant difference, and this result is desirable in terms of structure quality. Similar results were obtained by Ferjančič et al (2021) who evaluated the use of inulin, oat fiber and psyllium in chicken sausages, and which also did not change gumminess. Wongkaew et al (2020) observed that higher amounts of pectin from mango peel in Chinese sausages resulted in lower values of gumminess.…”
Section: Resultssupporting
confidence: 86%
“…In the study conducted by Akoglu et al (2015) in Turkish fermented sausages, addition of BC did not cause a significant difference, and this result is desirable in terms of structure quality. Similar results were obtained by Ferjančič et al (2021) who evaluated the use of inulin, oat fiber and psyllium in chicken sausages, and which also did not change gumminess. Wongkaew et al (2020) observed that higher amounts of pectin from mango peel in Chinese sausages resulted in lower values of gumminess.…”
Section: Resultssupporting
confidence: 86%
“…It is thought that the carotenoid pigments present in SPF cause an increase in the b * value. Significant increases in b * value have also been reported by studies conducted with dietary fiber from various sources in emulsified meat products (Ferjancic et al, 2021; Fernandez‐Gines et al, 2003; Viuda‐Martos et al, 2010a; Vivar‐Vera et al, 2018).…”
Section: Resultsmentioning
confidence: 66%
“…Significant increases in b* value have also been reported by studies conducted with dietary fiber from various sources in emulsified meat products (Ferjancic et al, 2021;Fernandez-Gines et al, 2003…”
Section: Colormentioning
confidence: 81%
“…Buckwheat constitutes a rich source of fiber, enhancing the water-holding capacity and protein-binding ability of the meat [ 45 ]. Many authors have confirmed the positive effect of added fiber sources, e.g., soy [ 46 ], sugarcane [ 47 ], oat [ 48 ], pumpkin [ 49 ], wheat and carrot [ 50 ], on water retention in meat products.…”
Section: Resultsmentioning
confidence: 99%